UPAYA MEMPERTAHANKAN KUALITAS PRODUK PASTRY DI HARRIS RESORT BARELANG BATAM - Hutagalung, Dhika Lariend; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The quality of a product is very important for a company in the field of pastry, including resorts, it all depends on the role of the person who processes a product. In addition to influencing purchasing decisions, positive reviews also build brand reputation, encourage word-of-mouth marketing, and provide valuable input for product development. This is the reason for the author to conduct research on how to maintain the quality of pastry products at HARRIS Resort Barelang Batam to continue to strive to provide quality products so as to get positive reviews from guests, then one of the resorts where the food products are market snacks are made by themselves and at every event there are always market snacks. The method used in this study is qualitative descriptive. The results of the research on the management of HARRIS Resort Barelang Batam are the determination of quality materials, accurate measurement of materials, the condition of the equipment needed, the use of proper procedures, and product storage procedures. After conducting research at HARRIS Resort Barelang Batam, it can be recommended to HARRIS Resort Barelang Batam, especially the staff of the pastry section to further improve and maintain the quality of pastry products by maintaining the production process according to existing SOP standards. Create unique and attractive pastry products so that guests are satisfied with the results of pastry performance. Keywords: Pastry, Market Snacks, Efforts to Maintain Product Quality, Resorts, HARRIS Resort Barelang Batam